Seberapa Besar Kontribusi BPR di Provinsi Bali Terhadap Pertumbuhan Ekonomi di Bali - Jaya, Purnam; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 10, Oktober 2016 (pp. 1011 - 1167), 2016)
Rural bank in Bali have a considerable influence on economic growth in Bali through working capital loans in the banking sector. Expected with the contribution  of rural banks, an increasing number if SMEs in Bali in particular. The purpose of this study was : 1) to determine the effect of interest rates on loans, non performing loans, and inflation simultaneously and partially to working capital credit rural banks value in Bali. This study using secondary data from Bank Indonesia (Central Bank) within period of eight years from 2007-2014, and calculated per three months.  The analysis technique used is multiple linear regression and classical assumption. The result of the analysis, the data showed simultaneous interest rate loans, non performing loans, and inflation significantly influence the value of working capital loans of rural banks in Bali. Partially, interest rates loans has negative and significant, non performing loans had no negative effect, and inflation is positive and significant impact on the value of working capital loans of rural banks in Bali
Keywords: Working Capital Loan, Loan Interest Rate, Non Performing Loan (NPL), Inflation